2019
DOI: 10.1002/jcb.29003
|View full text |Cite
|
Sign up to set email alerts
|

LXRα‐mediated downregulation of EGFR suppress colorectal cancer cell proliferation

Abstract: Liver X receptors (LXRs) are members of the nuclear receptor family, including the LXRα (NR1H3) and LXRβ (NR1H2) subtypes, which are related to the metabolism of glucose and cholesterol and possess anti‐inflammatory functions. Mounting evidence has linked LXRs to the inhibition of cell proliferation in a variety of cancers. We revealed a differential distribution for NR1H3, but not for NR1H2, in colorectal cancer and adjacent normal tissues. We found that NR1H3 enhanced the inhibitory action of GW3965, an agon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 47 publications
(96 reference statements)
1
9
0
Order By: Relevance
“…Liver X receptors, including LXR-α and LXR-β, are liganddependent nuclear receptors, which have more anti-proliferative effects on a variety of cancer cells (28)(29)(30)(31). Our results demonstrated that LXR-α had more anti-proliferative effects on prostate cancer cell lines than LXR-β (Figures 1, 2).…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Liver X receptors, including LXR-α and LXR-β, are liganddependent nuclear receptors, which have more anti-proliferative effects on a variety of cancer cells (28)(29)(30)(31). Our results demonstrated that LXR-α had more anti-proliferative effects on prostate cancer cell lines than LXR-β (Figures 1, 2).…”
Section: Discussionmentioning
confidence: 57%
“…We also revealed a positive correlation between lower LXR-α levels and high-grade malignancy prostate cancer cell lines, and vice versa (Figures 1D,E). LXR-α has been implicated in growth regulation of a variety of cancer cells (28,47,48), but the regulation of prostate cancer cell growth has never been previously reported. Herein, we showed that LXR-α acts as a tumor suppressor in prostate cancer with the following lines of supporting evidence: (1) LXR-α is down-regulated in prostate cancer tissues and high levels of LXR-α predicts a biomarker for prostate cancer;…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Several studies have reported that overexpression of METTL3 may promote tumor cell proliferation, migration, and the invasion of various solid tumors in vitro , such as gastric adenocarcinoma, and colorectal cancer. 10 11 In contrast, there were studies that showed the upregulation of METTL3, which could inhibit proliferation, migration, and invasion functions in colorectal cancer and renal cell carcinoma cells. 12 13 To date, a few studies have reported the expressions and possible roles of METTL3 in OSCCs.…”
Section: Introductionmentioning
confidence: 99%